Rubik’s Revenge Application Tool - Subaramya, V. (South Eastern University of Sri Lanka, 2016)
The Rubik's revenge is really captivating and fascinating puzzle. It is a three dimensional game. In the literary survey, there are several applications available in Rubik’s revenge. Some of them are in two dimensional games, some of them has not whole cube rotation using mouse. In this work, we introduces a new user friendly application tool which has three dimensional Rubik’s Revenge. To play the game using this application tool user can rotate whole cube using mouse and rotate each layer using buttons. If the user is not familiar with solving Rubik’s revenge, they can use the help menu. It has the algorithm for solve the Rubik’s Revenge. Learning to solve the Rubik's revenge helps teach many life lessons such as following direction, perseverance, memorization and focus